Clinical and Biological Predictors of Sustained Remission in Rheumatoid Arthritis Under Biologic Treatment - Federica P. Romano, Rahul S. Madhuri, Anuja D. Canfora (Open Journal of Physicians and Surgeons, 2025)
Background Rheumatoid arthritis (RA) is a chronic inflammatory disease that can lead to significant morbidity. Biologic disease-modifying antirheumatic drugs (DMARDs) have revolutionized treatment, but not all patients achieve sustained remission. Objective This study aims to identify predictors of sustained disease remission in patients with rheumatoid arthritis treated with biologic DMARDs. Methods A longitudinal cohort study was conducted involving 250 patients with RA receiving biologic DMARDs from 2020 to 2025. Sustained remission was defined as achieving a Disease Activity Score (DAS28) of <2.6 for at least six months. Demographic data, clinical characteristics, and laboratory findings were collected. Logistic regression analysis was used to identify factors associated with sustained remission. Results Of the 250 patients, 120 (48%) achieved sustained remission. Significant predictors included early treatment initiation (OR 2.5, p < 0.01), lower baseline DAS28 scores (OR 1.8, p < 0.01), and the presence of seronegative RA (OR 1.6, p < 0.05). Additionally, patients with a higher adherence to therapy demonstrated a greater likelihood of sustained remission (OR 3.0, p < 0.01). Conclusions Early treatment initiation, lower baseline disease activity, seronegativity, and high adherence to therapy are significant predictors of sustained disease remission in RA patients treated with biologic DMARDs. These findings emphasize the importance of early intervention and patient education in managing rheumatoid arthritis effectively.